Name-bearing Types of Neuropterida (Insecta) in the National Museums of Scotland, Edinburgh - Whittington, Andrew E. (Zootaxa, 2005)
A list of primary types for the superorder Neuropterida, held in the National Museums of Scotland Entomology Collection, is presented. The list provides the original name, the current valid combination to which the species is presently assigned, as well as the quoted label data and statements concerning the condition of the specimens. Holotypes of the following taxa are present: Brevibarbis waterstoni Tjeder & Hansson, 1992; Ptyngidricerus venustus Tjeder & Waterston, 1977; Chrysopa tigridis Morton, 1921; Boriomyia persica Morton, 1921; Sympherobius sanctus Tjeder, 1940; Gepus buxtoni Morton, 1921; Nelees mesopotamiae Morton, 1921; Apocroce spuria Tjeder, 1975; Parasicyoptera guichardi Tjeder, 1974. Syntypes of the following taxa are present: Sialis morio Klingstedt, 1933; Hemerobius contumax Tjeder, 1932; Hemerobius eatoni Morton, 1906; Hemerobius fenestratus Tjeder, 1932; Kimminsia killingtoni Morton, in Fraser 1942; Macronemurus delicatulus Morton, 1926. A lectotype is present for Hemerobius mortoni McLachlan, 1899.